2018
DOI: 10.1088/1741-2552/aa9820
|View full text |Cite
|
Sign up to set email alerts
|

Distributed stimulation increases force elicited with functional electrical stimulation

Abstract: It seems reasonable to consider using multi-electrode stimulation to augment the force-generating capacity of muscles and thereby increase the utility of FES systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 77 publications
4
30
0
Order By: Relevance
“…Previous studies [12][13][14][29][30][31] have tried to use dispersed muscle activation to reduce the force decline during continuous stimulations. Most of the studies have demonstrated that dispersed muscle activation can delay the fatigue onset compared with synchronized muscle activation [12-14, 30, 31].…”
Section: Dispersed Muscle Activation and Fatiguementioning
confidence: 99%
“…Previous studies [12][13][14][29][30][31] have tried to use dispersed muscle activation to reduce the force decline during continuous stimulations. Most of the studies have demonstrated that dispersed muscle activation can delay the fatigue onset compared with synchronized muscle activation [12-14, 30, 31].…”
Section: Dispersed Muscle Activation and Fatiguementioning
confidence: 99%
“…This problem of rapid fatigue has mainly been approached via attempts to distribute the load across multiple groups or regions of muscle. Various groups have attempted to solve this NMES limitation by utilizing multi-electrode pads and multi-source stimulations [18][19][20]. These studies showed that muscle fatigue can by delayed by distributing the stimulations across different areas both temporally and spatially.…”
Section: Fatigue and Stimulation Efficiencymentioning
confidence: 99%
“…For example, the tuning of various stimulation parameters (current amplitude, frequency, and pulse width) that can delay fatigue has been investigated [14][15][16][17]. Another approach is to have dispersed stimulation locations involving spatially and/or temporally distributed stimulation across multiple electrodes over the muscle belly [18][19][20]. This approach can alternate the activation of different groups of motor axons, which can alleviate the repeated load on recruited motor units and therefore delay fatigue onset.…”
Section: Introductionmentioning
confidence: 99%
“…The force scale factor in Equation (3) can be determined by the peak force for a given amplitude of the pulse [ 30 ]. In previous studies, the peak force was measured over a wide range of pulse amplitudes for the lower limb muscles, and the peak force–amplitude relationships could be represented using a sigmoid function, as shown in Figure 3 [ 23 , 53 , 54 , 55 ]. Although the peak force varies with the pulse amplitude between a motor threshold ( ) and a saturation threshold ( ), which represent the minimum pulse amplitudes for triggering and saturating the muscle contraction force, respectively, the full range of the pulse amplitude need not be considered for determining in EMS-based haptic rendering.…”
Section: Methodsmentioning
confidence: 99%